Penerapan Model Problem Based Learning (PBL) Untuk Meningkatkan Hasil Belajar Siswa Pada Pelajaran Ilmu Pengetahuan Sosial Kelas VI SDN Inpres 5/81 Tendeki - Lola, Marjuni Tiku; Katuuk, Deitje A.; Sumilat, Margareta O. (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to improve social studies learning outcomes in the material "Natural Appearances and Artificial Appearances" by applying the Problem Based Learning (PBL) model in class VI SDN Inpres 5/81 Tendeki. The research uses the Classroom Action Research (PTK) method proposed by Kemmis and Mc. Targgart. Which consists of two cycles where each cycle consists of four stages, namely: planning, implementing actions, observing and reflecting. The research results showed that the percentage of learning outcomes obtained by students in cycle I was 59.42% and in cycle II it increased to 83.76%. Based on the results of this research, it was concluded that the Problem Based Learning (PBL) model improved social studies learning outcomes for class VI students at SDN Inpres 5/81 Tendeki. In conclusion, the researcher suggests that teachers are expected to use the Problem Based Learning (PBL) model as an alternative in learning because it can help teachers improve student learning outcomes in social studies subjects in elementary schools (SD).